2022
DOI: 10.1001/jamanetworkopen.2022.35995
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sodium-Glucose Cotransporter-2 Inhibitors With Incident Atrial Fibrillation in Older Adults With Type 2 Diabetes

Abstract: ImportanceSodium-glucose cotransporter-2 inhibitors (SGLT-2is) have demonstrated many cardiovascular and kidney function benefits for patients with type 2 diabetes (T2D). However, the results of SGLT-2i use in primary prevention of atrial fibrillation (AF) were inconsistent in clinical trials, and incident AF was not a prespecified end point.ObjectiveTo examine incident AF with initiation of an SGLT-2i compared with initiation of a dipeptidyl peptidase-4 inhibitor (DPP-4i) or a glucagonlike peptide-1 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
3
4
0
Order By: Relevance
“…We observed that SGLT2i use was associated with a lower risk of incident AF compared with GLP-1RA use, consistent with the existing literature [ 31 ]. SGLT2i use was shown to be associated with lower risk of incident AF compared with placebo [ 7 ].…”
Section: Discussionsupporting
confidence: 91%
“…We observed that SGLT2i use was associated with a lower risk of incident AF compared with GLP-1RA use, consistent with the existing literature [ 31 ]. SGLT2i use was shown to be associated with lower risk of incident AF compared with placebo [ 7 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pleomorphic effects of SGLT2i have been proposed in the pre‐clinical studies that can be the plausible mechanisms for mitigating the risks of cognitive decline, including reducing oxidative stress, neuroinflammation, and improving brain mitochondrial function 36–38 . In addition to the protective metabolic pathways in the neurological system, initiation of SGLT2i was also found to be associated with a lower risk of incident or recurrent AF in diabetic patients 39,40 . Compatible with previous studies, our study also showed that patients receiving SGLT2i were associated with reduced AF events, which can be the possible explanation of the lower risk of subsequent cerebral cardio‐embolisation and cognitive impairment.…”
Section: Discussionsupporting
confidence: 79%
“…However, there is not yet evidence that SGLT2is prevent stroke in these patients. When compared with DPP-4 inhibitors or GLP-1 RA, the risk of incident AF was significantly lower with SGLT2is [1192].…”
Section: Hypertension In Established Cardiovascular Disordersmentioning
confidence: 91%